Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
x = -5
Step-by-step explanation:
I) Substitute:
3x + 2y = -5
3x + 2(5) = -5
3x + 10 = -5
II) Solve:
3x + 10 = -5
3x = -15 (Subtract 10 from both sides)
x = -5 (Divide both sides by 3)
Answer:
x = -5
y = 5
Step-by-step explanation:
We are given the system of equations :
3x + 2y = -5
y = 5
This can be solved through the process of substitution, mainly because y in the second equation already has a value in of its own and can be replaced with the y in the first equation. Therefore :
3x + 2y = -5
y = 5
3x + 2(5) = -5
3x + 10 = -5
Solve for x, first by subtracting ten by both sides :
3x = -15
Divide 3 by both sides to isolate x :
x = -5
Now that we have x, we have solved our system of equations, but let's prove it first.
x = -5
y = 5
3(-5) + 2(5) = -5
-15 + 10 = -5
Therefore, our two variables are x = -5 and y = 5
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.